Biometrical analysis of three species of the genus Lapeirouseia from the Campanian-Maastrichtian of Stranice (North-East Slovenia) - Caffau, Mauro (Geologija, 2000)
The rudist rich deposits of the region of Styria in the north-eastern Sloveniaare known since the beginning of the 20th century. Three Lapeirouseia species distributed from Campanian to Maastrichtian are found in this outcrop of the Upper Cretaceous. The biometrical analysis of the species Lapeirouseia zitteli Douvillé, Lapeirouseia laskarevi Milovanović and Lapeirouseia plana Milovanović showed that these three species constitute a single phylogenetic line.
Keywords: apnenec; biometrija; fosili; kreda; Lake Kreda; Slovenia; Slovenija; Stranice; stratigrafija; stratigraphy; školjke